2020
DOI: 10.1117/1.jrs.14.016504
|View full text |Cite
|
Sign up to set email alerts
|

How much benthic information can be retrieved with hyperspectral sensor from the optically complex coastal waters?

Abstract: The Baltic Sea represents an optically complex case 2 water type, where high concentrations of water column constituents limit acquisition of benthic information. Different preprocessing steps were applied to the hyperspectral compact airborne spectrographic imager (CASI) image to extract as much useful benthic information as possible. Atmospheric correction, minimum noise fraction transform, and sun-glint correction were performed to acquire water surface reflectance data. Additionally, a water column removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 64 publications
2
30
0
Order By: Relevance
“…The results in this work are remarkable particularly when compared with a recent study that estimated the detectability limits for seabed estimation for the CASI hyperspectral sensor in the complex waters of the Baltic sea [10]. Vahtmäe et al observed that the detectability threshold for the brightest seabed composed of sand was 7.5 m, 5 m for brighter benthic flora of green macroalgae, and 3 m for darker benthic flora composed of higher plants and brown macroalgae.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…The results in this work are remarkable particularly when compared with a recent study that estimated the detectability limits for seabed estimation for the CASI hyperspectral sensor in the complex waters of the Baltic sea [10]. Vahtmäe et al observed that the detectability threshold for the brightest seabed composed of sand was 7.5 m, 5 m for brighter benthic flora of green macroalgae, and 3 m for darker benthic flora composed of higher plants and brown macroalgae.…”
Section: Discussionsupporting
confidence: 56%
“…Despite multiple limitations, the hyperspectral remote sensing has developed as a potentially promising technology to study marine and freshwater benthic maps as well as bathymetry [10]. The detectable information is restricted within a maximum depth depending on the sensor characteristics and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations